2020
DOI: 10.46843/jiecr.v1i2.15
|View full text |Cite
|
Sign up to set email alerts
|

The Trend in Using Online Meeting Applications for Learning During the Period of Pandemic COVID-19: A Literature Review

Abstract: The pandemic COVID-19 has given a very significant impact on the lives of the world community, especially in the field of education. The existence of remote learning is an alternative for the community to reduce the impact of outbreaks. This alternative changes the direction of physical learning into online and virtual learning. The use of online meeting applications is an option that provides many conveniences for students and teachers to achieve learning goals without being in class. Various types of applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 11 publications
3
60
0
6
Order By: Relevance
“…The SARS Coronavirus (SARS-CoV) also harms conventional educational activities in most countries around the world. It forces academic experts to reconsider the conventional learning method (face-to-face learning) and begin to shift to distance online learning as a viable option for learning before conventional activities can be continued (Adnan & Anwar, 2020;Pratama et al, 2020). There has been a sudden and massive shift from conventional learning to online learning using the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…The SARS Coronavirus (SARS-CoV) also harms conventional educational activities in most countries around the world. It forces academic experts to reconsider the conventional learning method (face-to-face learning) and begin to shift to distance online learning as a viable option for learning before conventional activities can be continued (Adnan & Anwar, 2020;Pratama et al, 2020). There has been a sudden and massive shift from conventional learning to online learning using the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…This study is focused on the implementation of distance learning using AR-based multimedia acts as the solution to the learning process during COVID-19 pandemic. Moreover, the current science learning process ineffective in which students are unmotivated, and it impacts on the students' learning achievements and skills (Pratama et al, 2020;Reimers et al, 2020). It has been proved that if learners are less motivated during their learning process, it can impact on their learning achievements and skills (Rapanta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Both teachers from rural and urban areas prefer using virtual conference applications to teach. Not only did it become the trends (Pratama, Azman, Kassymova, & Duisenbayeva, 2020), but some studies (Kusuma & Hamidah, 2020;Yao, Rao, Jiang, & Xiong, 2020) also suggested them. However, teachers from rural schools have to consider their students' internet quota by focusing more on the WhatsApp group or providing a recorded video that still has effectiveness (Morgan, 2020;Yensy, 2020).…”
Section: Resultsmentioning
confidence: 97%